Sistem Pencatatan Hasil Timbangan Menggunakan Sensor Load Cell Melalui Database Berbasis Arduino Uno - Dhanneswara Yoga Widagdo (Jurnal Jaringan Telekomunikasi, 2020)
The system of weighing goods on the market today still uses a manual system. It can be seen in traditional markets that sell fruits and meat whose weighing system only provides output in the form of object weight and price without saving the results of the data and has not automatically sent measurement data to the database. The purpose of this tool is to solve the problem, to provide information about the type of material that is weighed by pressing the material code on the keypad and provide load weight data and total weighing price measurement results to the customer and send the data of into a database so the owner businesses can monitor the results of weight materials and the total price and can verify the income. The result is to provide scale measurement data about material's name, ingredient's weight and the total price of ingredients. The data is sent to the database and then the incoming data will be recorded from NodeMCU and the data will appear on the website or SmartPhone.The conclusion is the calibration process using a 20Kg Load Cell sensor gets a calibration_factor of 48530 to get a value of 0.00Kg and a readability of 10 grams. The tool has 10 codes that have been made, each code has a type of material and a different price for each button. Delay time of sending data is about 0.051 to 0.197 ms, which means excellent quality according to the TIPHON standard.